From data to knowledge – big data needs stewardship, a plant phenomics perspective. (5th June 2022) - Arend, Daniel; Psaroudakis, Dennis; Memon, Junaid Altaf; Rey‐Mazón, Elena; Schüler, Danuta; Szymanski, Jedrzej Jakub; Scholz, Uwe; Junker, Astrid; Lange, Matthias
SUMMARY: The research data life cycle from project planning to data publishing is an integral part of current research. Until the last decade, researchers were responsible for all associated phases in addition to the actual research and were assisted only at certain points by IT or bioinformaticians. Starting with advances in sequencing, the automation of analytical methods in all life science fields, including in plant phenotyping, has led to ever‐increasing amounts of ever more complex data. The tasks associated with these challenges now often exceed the expertise of and infrastructure available to scientists, leading to an increased risk of data loss over time. The IPK Gatersleben has one of the world's largest germplasm collections and two decades of experience in crop plant research data management. In this article we show how challenges in modern, data‐driven research can be addressed by data stewards. Based on concrete use cases, data management processes and best practices from plant phenotyping, we describe which expertise and skills are required and how data stewards as an integral actor can enhance the quality of a necessary digital transformation in progressive research. Significance Statement: The IPK Gatersleben has one of the world's largest germplasm collections and based on our years of experience in data management of large‐scale plant research data, we described our past and current strategies and attempted to identify requirements for data stewardship. In addition to the activities at our research facility, we actively participate in various international networks and standardization committees. This influences the work at our research institute and also transfers our experience to the external initiatives. We are convinced that this experience will be of interest to the readers of The Plant Journal and would be very pleased to receive a corresponding evaluation of our contribution.